School Committee Supporting Agency Model in Supporting Education Financing - M. Saman, Asrina; Nur Mahmudah, Fitri; Suyatno, Suyatno (International Journal of Educational Management and Innovation, 2024)
Financing in the implementation of the education process becomes a benchmark for the success of each planned program. Financing is a major problem in the existing education system. This study aims to explore the Education financing model carried out by the school committee. This research uses a qualitative type of research approach conducted with a case study at SMP Muhammadiyah 1 Weleri, Kendal Regency, Central Java Province. The sampling technique uses purposive sampling, and data collection through in-depth interviews then data analysis with the help of Atlas. ti software version 8. The results of the study explained that the school committee supports education financing, including supporting agencies, funding and support, financing programs, and financing resources. As a recommendation for education financing carried out by the school committee, the financing model carried out by the school committee has proven effective in supporting education financing, can help each school program, and build good relationships between schools, communities, and stakeholders in providing financing support.